Induction of Identical IgG HIV-1 Envelope Epitope Recognition Patterns After Initial HIVIS-DNA/MVA-CMDR Immunization and a Late MVA-CMDR Boost - Joachim, Agricola; Ahmed, Mohamed I. M.; Pollakis, Georgios; Rogers, Lisa; Hoffmann, Verena S.; Munseri, Patricia; Aboud, Said; Lyamuya, Eligius F.; Bakari, Muhammad; Robb, Merlin L.; Wahren, Britta; Sandstrom, Eric; et al. (Frontiers in Immunology, 2020)
In the RV144 trial, to date the only HIV-1 vaccine efficacy trial demonstrating a modestly reduced risk of HIV-1 acquisition, antibody responses towards the HIV Envelope protein (Env) variable (V) 2 and V3 regions were shown to be correlated with a reduced risk of infection. These potentially protective antibody responses, in parallel with the vaccine efficacy, however, waned quickly. Dissecting vaccine-induced IgG recognition of antigenic regions and their variants within the HIV-1 Env from different vaccine trials will aid in designing future HIV-1 immunogens and vaccination schedules. We, therefore, analysed the IgG response towards linear HIV-1 Env epitopes elicited by a multi-clade, multigene HIVIS-DNA priming, and heterologous recombinant modified vaccinia virus Ankara (MVA-CMDR) boosting regimen (HIVIS03) and assessed whether a late MVA-CMDR boost three years after completion of the initial vaccination schedule (HIVIS06) restored antibody responses towards these epitopes. Here we report that vaccination schedule in the HIVIS03 trial elicited IgG responses against linear epitopes within the V2 and V3 tip as well as against the gp41 immunodominant region in a high proportion of vaccinees. Antibodies against the V2 and gp41 Env regions were restricted to variants with close homology to the MVA-CMDR immunogen sequence, while V3 responses were more cross-reactive. Boosting with a late third MVA-CMDR after three years effectively restored waned IgG responses to linear Env epitopes and induced targeting of identical antigenic regions and variants comparable to the previous combined HIVIS-DNA/MVA-CMDR regimen. Our findings support the notion that anti-HIV-1 Env responses, associated with a reduced risk of infection in RV144, could be maintained by regular boosting with a single dose of MVA-CMDR.